Change of Boron Substitution Improves the Lasing Performance of Bodipy Dyes: A Mechanistic Rationalisation. Issue 2 (13th November 2012) - Jagtap, Krishna K.; Shivran, Neelam; Mula, Soumyaditya; Naik, Devidas B.; Sarkar, Sisir K.; Mukherjee, Tulsi; Maity, Dilip K.; Ray, Alok K.
Abstract Bodipy laser dyes are highly efficient but degrade rapidly in solution by reacting with in situ generated singlet oxygen (1O2). To increase the lasing lifetimes of these dyes, we have designed and synthesised two different congeners of the widely studied Pyrromethene 567 (PM567) by substitution at the boron centre and/or at both the boron centre and the meso position. The two new dyes showed high lasing efficiencies with increased photostability. The results of theoretical and pulse radiolysis studies revealed that the substitution at the boron centre reduced the 1O2 generation capacity of these dyes as well as their rate of reaction with 1O2, thereby enhancing their lifetimes even under lasing conditions.